Hubungan Antara Lingkungan Kerja Dengan Kepuasan Kerja Pada Pegawai Badan Narkotika Nasional Provinsi Sumatera Utara - Afifah Amalia Daulay; Doli Maulana Gama Samudera Lubis (Universitas Medan Area, 2023)
This article aims to examine the correlation between the work environment and employees job satisfaction in National Narcotics Agency of North Sumatra Province. The number of samples in this study was 73 employees who were registered as permanent employees. The sample collection technique in this research uses total sampling technique. Data collection wqs carried out using a Likert scale model for work environment and job satisfaction. The results of the research using the product moment correlation technique (r_xy ) are known to be 0,424 with p = 0,000 0,05. This means that there is a positive relationship correlation between work environment and job satisfaction in employees, the more positive work environment, the more positive the job satisfaction and the hypothesis in this study is accepted. Work environment contributed 18,0% to job satisfaction.